2018
DOI: 10.1007/s00330-018-5682-x
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA-PET/CT in comparison with 18F-fluoride-PET/CT and whole-body MRI for the detection of bone metastases in patients with prostate cancer: a prospective diagnostic accuracy study

Abstract: • PSMA-PET/CT assessed the presence of bone metastases correctly in all 55 patients • PSMA-PET/CT was more advantageous compared to WB-MRI • No difference was found between PSMA-PET/CT and NaF-PET/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 45 publications
0
53
1
1
Order By: Relevance
“…PSMA PET/CT showed superior diagnostic performance compared to anatomical imaging for lymph node staging in studies where comparative data were reported. Since studies have shown PSMA PET/CT to outperform bone scans, with or without SPECT/CT, for the detection of skeletal metastases [45][46][47][48], PSMA PET/CT may turn out to be a one-stop modality for staging in these patients.…”
Section: Resultsmentioning
confidence: 99%
“…PSMA PET/CT showed superior diagnostic performance compared to anatomical imaging for lymph node staging in studies where comparative data were reported. Since studies have shown PSMA PET/CT to outperform bone scans, with or without SPECT/CT, for the detection of skeletal metastases [45][46][47][48], PSMA PET/CT may turn out to be a one-stop modality for staging in these patients.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zacho et al recently performed a prospective study on 68 patients with biochemically recurrent PCa and found that Na 18 F and a 68 Galabeled PSMA-targeted PET radiotracer had similarly high rates for identifying PCa bone metastases (22). Further, a patient-level analysis by Dyrberg et al of patients with PCa undergoing imaging with both Na 18 F and a 68 Ga-labeled PSMA-targeted PET radiotracer also found no difference in diagnostic ability between the agents (23).…”
Section: Discussionmentioning
confidence: 99%
“…When 18 F-FDG and 18 F-NaF are compared, the latter is more sensitive for detecting bone metastases at BCR even at PSA levels as low as 2-4 ng/mL, albeit at the expense of specificity (46)(47)(48). For PSMA tracers, mostly in a mixed primary and recurrent population, studies show a similar pattern, with 18 F-NaF detecting more bone lesions at the expense of decreased specificity (49-51); 1 study showed no significant difference (52). A consistent result is that, compared with other PET tracers, 18 F-NaF is more sensitive for bone lesions at the expense of specificity.…”
Section: Clinical Categories and Auc Scoresmentioning
confidence: 95%